The triglyceride-glucose index is associated with a higher risk of hypertension: evidence from a cross-sectional study of Chinese adults and meta-analysis of epidemiology studies - Ren, Xiaoli; Chen, Mengying; Lian, Liyou; Xia, Huimin; Chen, Wei; Ge, Shengjie; Yang, Lijuan; Jiang, Qingxi; Gu, Xuejiang; Yang, Bo; Hu, Xiang (Frontiers in Endocrinology, 2025)
BackgroundThe results of population-based studies show a diverse association between the triglyceride-glucose (TyG) index and hypertension. The present study aimed to investigate this association based on a cross-sectional study on Chinese adults and meta-analysis of epidemiology studies.MethodsThe cross-sectional analysis used the baseline data from the on-going REACTION study in China. The TyG index was calculated as Ln [triglyceride(mg/dl)×fasting plasma glucose(mg/dl)/2]. A multivariate-adjusted logistic regression model was used to calculate the odds ratio (OR) with a 95% confidence interval (CIs) for the prevalence of hypertension, with the lowest TyG quartile as a reference.ResultsA total of 4,177 participants aged 58.62 ± 8.40 years were included. TyG was significantly associated with higher odds of hypertension (OR:1.273, 95% CI:1.171-1.384), and the association remained pronounced with isolated systolic hypertension (OR:1.161, 95% CI:1.045-1.289) and systolic-diastolic hypertension (OR:1.313, 95% CI:1.163-1.483) but not with isolated diastolic hypertension (OR:1.164, 95% CI:0.929-1.460). In the present meta-analysis, 34 relevant studies were included through systematic searches of PUBMED, Embase, and the Cochrane Library. A positive association between the TyG index and hypertension was revealed in the meta-analysis of cohort studies (HR:1.57, 95% CI:1.25-1.96) and cross-sectional studies (OR:2.01, 95% CI:1.47-2.76).ConclusionElevated TyG index levels were significantly associated with a higher risk of clinical hypertension, which may provide new insights into the clinical management of hypertension.